An investigation of possible relationships between certain Rorschach determinants and concomitant physiological measurements - Broekmann, N. C.(Neil Charles),1942- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1969.